Clinical and pathological characteristics, pathological reevaluation and recurrence patterns of cellular leiomyomas: a retrospective study in 76 patients - Rothmund, Ralf; Kurth, Ralf-Rainer; Lukasinski, Nadia-Maria; Huebner, Markus; Hartkopf, Andreas; Wallwiener, Markus; Staebler, Annette; Brucker, Sara Y.; Taran, Florin Andrei (European journal of obstetrics & gynecology and reproductive biology, 2013)
Objectives - To analyze clinical and pathologic features as well as recurrence patterns of cellular leiomyomas (CL) in women who underwent surgical therapy for symptomatic disease. - Study design - This retrospective study was conducted at the Department of Obstetrics and Gynecology, University Women's Clinic, Tuebingen, Germany. We identified all women who had CL on final diagnosis after surgery between January 1, 2000, and December 31, 2010. - Results - Our study sample comprised 76 women with a diagnosis of CL. A single uterine mass was present in 51.3% of the cases; in uteri with both CL and uterine leiomyomas (UL), the CL constituted the largest uterine mass in 20 of 21 (95.2%) cases. Additionally, in 98% of the uteri, CL were either the largest or the only uterine mass. Five women (6.6%; 5/76) had reported surgical procedures for symptomatic leiomyoma before the index surgery in our analysis. Three women underwent hysteroscopic resection of the leiomyomas and 2 women underwent abdominal myomectomy. Mean time to recurrence was 14.0 months (median 6.0; range, 4.0-52.0). Over the follow-up period, 6 women who underwent uterus-conserving surgery (12.0%; 6/50) with CL had leiomyoma recurrence. Five women underwent abdominal myomectomy and one underwent hysteroscopic resection of the CL. One patient had recurrence of a CL 43 months after abdominal myomectomy and underwent vaginal hysterectomy; the other five women had recurrences of UL. Mean time to recurrence was 28.6 months (median 12.5; range, 4.0-83.0). - Conclusions - Recurrence rates of CL in our study group resemble recurrence rates of UL.
Gesehen am 21.01.2022